Implementation of the 2023 Community Service Lecture (CSL) for STIT Muhammadiyah Abdya Students in Two Regencies: Synergy of Education and Community Empowerment - Razie, T. Fachrul; Baidullah, Baidullah; Abidin, Zainal; Authar, Tanzilul; Abdillah, Zakie; Musbir, Musbir (Journal Informatic, Education and Management (JIEM), 2026)
Community Service Lecture (CSL) activities are an integral part of the implementation of the Tri Dharma of Higher Education, especially in the aspect of community service. This program was implemented by STIT Muhammadiyah Aceh Barat Daya in 2023 in two locations, namely Central Aceh Regency and Southwest Aceh Regency, with the theme "Strengthening the Values ​​of Religious Education, Health, and Economic Empowerment Based on Community Service." The main objective of this activity is to improve the quality of life of the community through strengthening religious values, health awareness, and economic empowerment based on local potential. The implementation method includes a participatory approach involving village officials, religious leaders, health institutions, and government agency partners, including the National Population and Family Planning Board (BKKBN) in implementing the DASHAT (Healthy Kitchen to Overcome Stunting) activity. The results of the activity show that (1) in the field of religious education, there has been an increase in public understanding and participation in religious activities; (2) in the health sector, people are more aware of the importance of clean living behavior and balanced nutrition; and (3) in the field of economic empowerment, the community is able to develop small business skills based on local products. In addition, collaboration with the National Population and Family Planning Board (BKKBN) through the DASHAT program has had a significant impact on increasing family nutrition awareness and preventing stunting at the village level. Overall, the implementation of KPM 2023 successfully integrated religious, health, and economic values ​​into sustainable community service activities. This activity not only provides direct benefits to the community, but also serves as a social learning medium for students to develop empathy, leadership, and social responsibility as future Muslim intellectuals with a spirit of service.